Specific Professional-Psychological Competencies Of The Managerial Personality And Thepsychological Portrait Of A Competent Leader (Eurasian Journal of Humanities and Social Sciences, 2025)
This article analyzes the socio-psychological and professional competencies of a leader. The article analyzes the psychological components of a leader and cultured leader.